Visual Media in Social Studies Learning at SDN Umbul Kapuk Serang City - Yusup, Maulana; Hafidoh, Hafidoh; Ningtias, Diniya; Sofia Rizqia, Mila; Suhernah, Suhernah; Wijaya, Sastra (JUPE : Jurnal Pendidikan Mandala, 2024)
The purpose of this study is to describe and describe visual media in social studies learning at SDN Umbul Kapuk Serang City. This research uses a descriptive qualitative research approach method. The findings show that visual media is a medium that can help students to better understand the material to be delivered such as images, video impressions, diagrams and graphs. Related to the effectiveness of visual media in social studies learning in the classroom is very effective because students can know and recognize various forms or types such as knowing the shape of traditional houses and types or kinds of traditional clothing and so on. Image and video media are visual media that are taught and often taught in grade IV social studies learning at SDN Umbul Kapuk Serang City. Social studies learning is also very fun because it can know the surrounding environment, the state of the natural and human environment itself and the influence of visual media on student learning outcomes in class is very effective.